2006
DOI: 10.1111/j.1745-4573.2006.00051.x
|View full text |Cite
|
Sign up to set email alerts
|

EFFECT OF REFRIGERATED STORAGE ON PROTEOLYTIC ACTIVITY AND PHYSICOCHEMICAL AND MICROSTRUCTURAL PROPERTIES OF GIANT SQUID (DOSIDICUS GIGAS) MANTLE MUSCLE

Abstract: Giant squid (Dosidicus gigas) is abundant along the Pacific Coast of Mexico. It possesses a high proteolytic activity that makes it a low‐quality food material. Squid mantle endogenous proteases were partially characterized; physicochemical and structural changes during storage at 4C were also examined. High proteolytic activity was observed at acidic and alkaline pH values. Proteases were strongly inhibited by leupeptine and pepstatin A, as well as by phenyl methyl sulfonyl fluoride, indicating the possible p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 59 publications
2
9
0
2
Order By: Relevance
“…Muscle tissue in the state of rigor mortis loses its moisture when cooked and is particularly unsuitable for further processing that involves heating, since heat denaturation enhances water loss. Loss of water has a detrimental effect on the texture of fish muscle, and an inverse relationship has been found between muscle toughness and pH, unacceptable levels of toughness (and water loss on cooking) occurring at low pH levels (Huss 1995;Dublán-García et al 2006;Wang et al 2011). These findings are consistent with our results.…”
Section: Physicochemical Evaluation Of Musclesupporting
confidence: 95%
See 1 more Smart Citation
“…Muscle tissue in the state of rigor mortis loses its moisture when cooked and is particularly unsuitable for further processing that involves heating, since heat denaturation enhances water loss. Loss of water has a detrimental effect on the texture of fish muscle, and an inverse relationship has been found between muscle toughness and pH, unacceptable levels of toughness (and water loss on cooking) occurring at low pH levels (Huss 1995;Dublán-García et al 2006;Wang et al 2011). These findings are consistent with our results.…”
Section: Physicochemical Evaluation Of Musclesupporting
confidence: 95%
“…There are several proteolytic systems in fish muscle tissue which may be involved in post-mortem muscle degradation including proteasomes (heat-stable alkaline proteinases), matrix metalloproteinases, calpains, and lysosomal cathepsins. It has been suggested that cathepsins B, L, and/or D may have major roles in protein degradation in post-mortem fish muscle (Delbarre-Ladrat et al 2004;Dublán-García et al 2006;Wang et al 2011). Bondareva et al (2007) report substantially lower calpain activity in fish from Hg 2+ -contaminated lakes than that in control specimens as well as suppression of autolytic activity.…”
Section: Textural Evaluation Of Musclementioning
confidence: 95%
“…The loss of freshness in squid is known to be faster than that in other fish (Ohashi and others 1991; Yokoyama and others 1994). The activity of proteinase present in the squid mantle muscle is high (Kolodziejska and others 1987; Gómez‐Guillén and others 2003; Dublán‐García and others 2006), and therefore, squid muscle autolysis occurs rapidly (Vaz‐Pires and Seixas 2006). In our experiment, squid muscle tissue structure showed disintegration at the cellular level during storage under refrigeration for 24 h (4 °C) following all 4 methods of transportation (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…Several factors, such as physiological stage, feeding habits, size, catching methods, and storage temperature, resulted in different degradation rates among squid species. [3] Squid has a short life cycle and, therefore, its growth is rapid. This implies a high turnover rate of body proteins, which is associated with intense activities of the proteolytic enzymes.…”
Section: Introductionmentioning
confidence: 99%